MENUMBUHKEMBANGKAN DAYA MATEMATIS SISWA - Mumun Syaban (EDUCARE, 2008)
Mathematical power be abilitys which must be owned by student from and when doing mathematics. Mathematical power includes the ability to explore, conjecture, and reason logically; to solve non-routine problems; to communicate about and through mathematics; and to connect ideas within mathematics and between mathematics and other intellectual activity. The core concept of achieving mathematical power is that students develop mathematical power through problem solving, communication, reasoning, and connections.Kata Kunci: Mathematical Power, problem solving, reasonning, communication, and connection.